Reparação óssea em cirurgias de levantamento de seio maxilar, utilizando fosfato de cálcio bifásico em humanos, com e sem irrigação prévia de ácido épsilon-amino-cáproico (EACA) após 8 meses. Análise histológica - Martinez Júnior, Wilson (2009)
The indication of osseointegrated implants in atrophied posterior maxillary ridges reconstructed with the use of substitute bones has been extensively used, in recent decades, in surgeries which have 1 and 2 surgical stages. In this study, guided by the optical microscopy, we aimed to evaluate the bone repair obtained in the maxillary sinuses implanted with biphasic calcium phosphate and compare them to a group of patients who were previously irrigated with epsilon aminocaproic acid (EACA). Thus, eight patients undergoing maxillary sinus lifting procedures were part of the sample. In a period of eight months after this surgery, at the time of implants placement, the specimens were obtained from the grafts, through biopsies which were performed with trephine drills. The surgical equipments went through a routine histotechnical procedure and they were stained by Hematoxylin-Eosin (H.E.) Masson trichrome techniques. As a result, we could find bone in the remodeling process in both groups, confirming the osteoconductive potential of biomaterial, not evidencing a more accelerated process in the group with irrigation of EACA. Thus, we concluded that the period of eight months was sufficient for the incorporation of the implant, and the possible installation of the implants at that time. However, there were no significant changes regarding the acceleration of the repair process in the group with irrigation of EACA and the maintenance of the period of eight months for installation of implants is advisable.